Perancangan Sistem Pengolahan Isyarat ECG Untuk Diagnosis Menggunakan Lab VIEW 2009 Berbasis Wavelet - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Different physicians may interpret the same ECG signal differently. The aim of this research is to realize a system that can help thephysicians to interpret objectively the ECG signal for diagnostics purpose.. This research uses LabViEW software to process ECG signal. The signal which has been read ~ill then be analyzed using wavelet transforms. Wavelettransforms has been used over recent years to analyze nonstationary signals such as ECG signal. The result of this research is a diagnosticsystem with capability to analyze and diagnoze ECGsignal based on Heart Rate Variability(HRV).